Critical View of Safety in Laparoscopic Cholecystectomy: A Word of Caution in Cases of Aberrant Anatomy - Antonopoulou, Maria Ioanna; Manatakis, Dimitrios K. (The Surgery Journal, 2022)
Introduction To avoid vasculobiliary injuries, the Critical View of Safety (CVS) technique is strongly recommended during dissection of the hepatocystic triangle. It entails three basic steps as follows: (1) complete clearance of the hepatocystic triangle of fibrofatty tissue, (2) separation of the lower part of the gallbladder from the cystic plate, so that (3) two and only two structures are seen entering the gallbladder.Case History In this video vignette, we present the case of an aberrant hepatic artery, coursing subserosally parallel to the gallbladder wall. Despite presumably achieving all three CVS requirements, the surgeon did not proceed to clipping and dividing the two structures, preventing a major vascular injury. Due to its unusually large caliber, the artery was carefully dissected, and multiple smaller branches to the gallbladder were ligated instead, until it was definitively identified entering into the hepatic parenchyma of segments IVb–V.Discussion The CVS approach was originally conceived as a means for the conclusive recognition of the cystic duct and artery to prevent misidentification errors. However, in such cases of extreme anatomical variations, the CVS may indeed have certain limitations. Therefore the surgeon should always maintain a high degree of suspicion and a low threshold for alternative bail-out options.
Keywords: anatomy; gallbladder; laparoscopic cholecystectomy; vasculobiliary injury